Challenges and needs of informal caregivers in elderly care: Qualitative research in four European countries, the TRACE project. (March 2020) - Akgun-Citak, Ebru; Attepe-Ozden, Seda; Vaskelyte, Alina; van Bruchem-Visser, Rozemarijn L.; Pompili, Saverio; Kav, Sultan; Acar, Sema; Aksoydan, Emine; Altintas, Atahan; Aytar, Aydan; Baskici, Cigdem; Blazeviciene, Aurelija; et al.
Highlights: The informal caregiver plays an essential role in the home care. Providing informal care is not easy and may affect caregivers' life in different ways. All the caregivers from all countries had difficulties managing care, their own life, and coping with emotions. Educational programs focused to support and help to reduce burden of care for elderly with chronic diseases. Abstract: Background: Providing informal care may affects caregivers' life in different ways. Determining the needs of caregivers and supporting them can improve both the quality of life of the caregivers, as well as the elderly they take care of. Objective: To explore the experiences and needs of the informal caregivers in four countries. Design: Qualitative research method was used in the study. Methods: The qualitative data was collected through focus groups and individual interviews between December 2016–May 2017. In all countries interviews were conducted in the mother language of the informants. Informants of the qualitative research were adult people who take primary care of an individual with chronic diseases, aged 65 years or older. Data were collected from 72 informal caregivers from four European countries. Inductive content analysis was performed. Results: Informal caregivers identified 2 themes, 5 subthemes, 19 categories and 7 subtcategories. The themes highlighted two major issues: informal caregiver's challenges and needs related to the management of care of elderly and caregivers' personal needs. Conclusion: The important and charming results of the present study are, difficulties of managing caregiver's own life, and coping with emotions are common in four countries. Identifying challenges and needs of informal caregivers enable healthcare professionals to develop care strategies and plan interventions focused to support and help to reduce the burden of care for elderly with chronic diseases.